2015
DOI: 10.1080/09712119.2015.1124330
|View full text |Cite
|
Sign up to set email alerts
|

Physico-chemical properties of breast muscle in broiler chickens fed probiotics, antibiotics or antibiotic–probiotic mix

Abstract: This study investigated the efficacy of antibiotics, probiotics and their combination on meat quality of breast muscle in broilers. A total of 480 male one-day-old Cobb chicks were randomly assigned to control (without additive), antibiotic growth promoter (AGP), Bioplus ® (probiotics), or AGP + Bioplus ® and raised for 42 d. Each treatment was replicated six times with 20 birds per replicate. At the end of rearing period, 10 birds were randomly selected from each treatment, slaughtered and the breast muscles … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
31
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(45 citation statements)
references
References 31 publications
10
31
4
Order By: Relevance
“…Rahman & Kim (2016) reported that dietary supplementation of Nigella sativa seed (source of antioxidant) increased the protein content of broiler meat, whereas Marzoni et al (2014) showed no effect of dietary natural antioxidants (dry extracts of tomato skin, orange peel, and green tea leaves) on the crude protein content of breast and thigh meat of broiler chickens and Muscovy ducks. With regard to the effect of AGPs on crude protein content of meat, the present findings were different from those reported by other workers, which showed no effect of various AGPs, for example 0.05% chlortetracycline and HCL + cyanocobalamin (Yang et al, 2003), 0.5 g/kg flavomycin (Attia et al, 2011), 0.005% oxytetracycline (Hossain et al, 2012), and 100 ppm combination of oxytetracycline and neomycin (Abdulla et al, 2017). The rationale for this condition is not fully known, but the various types and doses of AGPs and the conditions of the study may partly explain the conflicting results.…”
Section: Discussioncontrasting
confidence: 57%
See 2 more Smart Citations
“…Rahman & Kim (2016) reported that dietary supplementation of Nigella sativa seed (source of antioxidant) increased the protein content of broiler meat, whereas Marzoni et al (2014) showed no effect of dietary natural antioxidants (dry extracts of tomato skin, orange peel, and green tea leaves) on the crude protein content of breast and thigh meat of broiler chickens and Muscovy ducks. With regard to the effect of AGPs on crude protein content of meat, the present findings were different from those reported by other workers, which showed no effect of various AGPs, for example 0.05% chlortetracycline and HCL + cyanocobalamin (Yang et al, 2003), 0.5 g/kg flavomycin (Attia et al, 2011), 0.005% oxytetracycline (Hossain et al, 2012), and 100 ppm combination of oxytetracycline and neomycin (Abdulla et al, 2017). The rationale for this condition is not fully known, but the various types and doses of AGPs and the conditions of the study may partly explain the conflicting results.…”
Section: Discussioncontrasting
confidence: 57%
“…The present finding was different from that of Nie et al (2015), who showed no effect of fermented cottonseed meal on crude ash of breast muscle of broiler chicks. Several studies have reported enhancing effects (Khaksefidi & Rahimi, 2005) and absent effects (Abdulla et al, 2017) of probiotics on the crude ash content of broiler meat. With regard to the effect of antioxidants on the ash content of broiler meat, Kim et al (2015) demonstrated that dietary supplementation with 1% sea urchin shell powder (rich in antioxidants) significantly reduced the ash content of broiler meat, whereas Marzoni et al (2014) and Rahman & Kim (2016) reported no effect of dietary natural antioxidant on ash content of meat from broiler chicks.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Above mention traits are closely linked to water holding capacity of meat, it is another significant characteristic of meat. When Bacillus subtilis fed to broiler chickens and meat from these chickens was stored for 7 days, during storage the significant decreased in pH was observed and this lower pH is beneficial for meat storage [75]. Significantly increase in the breast meat redness was observed when Lactobacillus fermentum was added in broiler drinking water as probiotics [76].…”
Section: Probiotics Effects On Chicken Meat Traitsmentioning
confidence: 99%
“…Probable growth-promoting replacements should maintain the beneficial actions of antibiotics, but eliminate undesirable side-effects, such as bacterial resistance. Such an alternative would be the use of probiotics, which are live microbial products that are beneficial to the host through an improved microbial equilibrium in the intestines (Abdulla et al, 2015). The most commonly used probiotic bacteria in poultry are Lactobacillus, Bifidobacterium, Bacillus, Streptococcus, Pediococcus and Enterococcus species (Manafi et al, 2018).…”
Section: Introductionmentioning
confidence: 99%